ADAPTATION AND OPTIMIZATION OF TRADITIONAL MARKETING STRATEGIES TO THE REQUIREMENTS OF THE DIGITAL ECONOMY: CHALLENGES AND OPPORTUNITIES - RAIKO, Diana; DREPIN, Ivan; MASALAB, Oleksandr (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The modern business sphere is undergoing significant transformations in the context of rapidly changing digital economy, presenting both serious challenges and unlimited opportunities for companies. This article is dedicated to analyzing this phenomenon, aiming to identify optimal ways of adaptation and enhancement of traditional marketing strategies in response to new realities. The relevance of adapting and optimizing traditional marketing strategies to meet the demands of the digital economy is crucial in today's business environment. With the advent of digital technologies and changes in consumer habits, companies must revise their strategies to effectively compete in the market. The digital economy requires not only an online presence but also an understanding and utilization of cutting-edge tools and approaches.A range of key challenges arising from the implementation of digital technologies in marketing activities are highlighted, including the instability of the digital environment, high pace of changes, market competition for innovations, and the need for new skills in personnel. Through a thorough analysis of contemporary requirements for marketing strategizing, the researcher in the article provides comprehensive recommendations for optimizing and adapting traditional strategies. Special emphasis is placed on the examination of innovative tools in digital marketing, such as social networks, data analytics, artificial intelligence, and machine learning. Examples of successful utilization of these tools to achieve strategic marketing goals are cited, and opportunities for personalization and audience interaction in a dynamic digital environment are outlined.Additionally, the article discusses ethical and legal aspects of using digital strategies in marketing, and highlights factors contributing to the successful implementation of digital marketing strategies in the modern business environment. The article serves as a valuable source for professionals in the fields of marketing, management, and business who seek not only to understand the challenges of digital transformation but also to implement effective strategies for success in a high-tech business environment.
Keywords: marketing; traditional marketing; traditional marketing strategies; economy; economic strategies; digital economy